(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. Sunflower (Helianthus annuus L.) is one of the most important oilseed crops worldwide and in Ukraine, and the increase in its productivity is largely associated with the development of new high-yielding heterotic hybrids. Under current conditions of climate change and increasing requirements for yield stability, the study of the genetic variability of economically valuable traits and the identification of relationships among yield structure components have become particularly relevant. A comprehensive evaluation of experimental hybrids based on morphological and productivity traits makes it possible to identify promising genotypes for further use in breeding programs. Purpose. The aim of the study was to conduct a comprehensive evaluation of experimental sunflower hybrids based on morphological traits and yield structure components, to determine the level of their variability, to identify relationships among the main productivity indicators, and to select promising hybrid combinations for use in breeding programs under the conditions of the Eastern Forest-Steppe of Ukraine. Methods. Field experiments were carried out in 2024–2025 under the environmental conditions of the Eastern Forest-Steppe of Ukraine. The experimental material included 68 sunflower hybrids obtained by crossing four sterile maternal lines with 20 fertility restorer lines developed through in-house breeding. Sowing was performed according to a 70 × 25 cm spacing scheme with three replications and randomized plot placement. The following traits were evaluated: plant height, number of leaves, head diameter, plant productivity, 1000-seed weight, seed bulk density, and biological yield. Statistical analysis was performed using variation analysis and principal component analysis (PCA). Results. A considerable variability of the studied traits among sunflower hybrids was revealed. Plant height ranged from 146 to 200 cm, head diameter from 13.1 to 19.3 cm, plant productivity from 32.0 to 88.3 g, 1000-seed weight from 35.1 to 71.4 g, and seed bulk density from 343 to 480 g L⁻¹. Biological yield varied from 1.8 to 4.9 t ha⁻¹. The highest productivity was recorded for hybrids A620-16×SD-054B (4.9 t ha⁻¹), A25×SD-057B (4.6 t ha⁻¹), and A25×SD-029B (4.4 t ha⁻¹). Principal component analysis showed that the first two components explained 59.6% of the total trait variability. A strong positive relationship between plant productivity and 1000-seed weight was identified, indicating their key role in yield formation. Conclusions. The studied collection of experimental hybrids is characterized by substantial genetic diversity in morphological and productivity traits, which creates broad opportunities for selection. Several hybrid combinations with high productivity and favorable yield structure components were identified. These hybrids can be considered promising breeding material for the development of new competitive sunflower hybrids adapted to the conditions of the Eastern Forest-Steppe of Ukraine.